Determinants of Support for Climate Change Efforts in the Global South - Adugu, Emmanuel (European Journal of Sustainable Development, 2020)
This paper addresses determinants that underpin support for climate change efforts. The study is based on Pew Research Center (USA), Spring 2015 Global Attitudes survey dataset, with a primary focus on climate change, collected from March 25 to May 27, 2015. Drawing on the new ecological paradigm and ecological modernization perspectives, the paper utilizing logistic regression, examines the relationship between individuals’ perception or awareness of the severity of climate change and their support for limiting greenhouse emissions; the extent to which individuals’ views on whether developing countries should do as much as the rich countries in addressing climate change predict the likelihood of their (individuals’) support for limiting greenhouse emissions. The logistic regression models reveal that people’s rational insight into the following consequences of climate change positively predicts support for limiting greenhouse emissions: severe weather like floods or severe storms; long periods of unusually hot weather; rising sea levels; years of schooling and age positively predict support for limiting greenhouse emissions. In general, knowing an individual’s country of residence offers no predictive value in determining whether the individual will support limiting greenhouse emissions. The notable exceptions are: South Africa, Nigeria, Ghana and Kenya. These four countries display positive and statistically significant coefficients in the logistic regression model predicting support for greenhouse emissions. Keywords: climate change; environmental concern; greenhouse emissions; ecological crisis; Africa